Indocyanine green-activated fluorescence laparoscopy imaging: a novel quantitative assessment method for intraperitoneal aerosolized drug distribution - Qiming Fan; Renjie Li; Xiaosong Lin; Zifeng Yang; Yong Li (Holistic Integrative Oncology)
Abstract Background Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is an emerging treatment for peritoneal metastasis. Although its aerosol distribution is known to be inhomogeneous, quantitative assessment remains limited. This study introduces a novel approach to quantify the PIPAC drug distribution by integrating indocyanine green (ICG) with fluorescent laparoscopy. Methods The optimal ICG concentration (0.1–100 μg/mL) was determined via gray value calibration. Aerosolized ICG (5 μg/mL) was sprayed into an ex vivo box model containing four fresh swine peritoneal samples positioned as follows: (A) bottom directly opposite the nozzle, (B) obstructive bottom, (C) side wall, and (D) top. Fluorescence laparoscopy images were analyzed using ImageJ. Ex vivo validation included doxorubicin (DOX) aerosolization to measure penetration depth. In vivo distribution was assessed in the rabbit abdominal cavities. Results Sample A exhibited the highest ICG deposition (gray value: 219.6 ± 1.0), significantly exceeding samples B (107.4 ± 16.7, p < 0.0001), C (126.9 ± 14.9, p = 0.012), and D (124.4 ± 17.3, p = 0.002). DOX penetration depth was greatest in sample A (342.1 ± 47.3 μm), surpassing B (205.6 ± 38.9 μm, p < 0.0001), C (301.3 ± 36.8 μm, p = 0.002), and D (197.4 ± 47.8 μm, p < 0.0001). In rabbits, maximal ICG accumulation varied anatomically: the bladder (Rabbit 1: 198.1; Rabbit 3: 189.8) and left flank (Rabbit 2: 208.1) showed the highest values, with significant regional heterogeneity. Conclusions This study establishes a fluorescence-based method to quantitatively evaluate PIPAC distribution, demonstrating inhomogeneous drug deposition and penetration both ex vivo and in vivo. These findings highlight the potential of ICG-guided imaging to optimize therapeutic efficacy in clinical PIPAC applications.